Конструктивні методи розв'язання одного класу крайових задач для нелінійних еліптичних рівнянь - Луханін, В. С. (ХНУРЕ, 2019)
Дисертація присвячена розробці конструктивних методів знаходження додатних розв’язків одного класу крайових задач для нелінійних еліптичних рівнянь та знаходженню умов, яким мають задовольняти параметри задачі, щоб гарантувалися існування та єдиність розв’язку, а також збіжність відповідного ітераційного процесу. У роботі вперше виділено клас крайових задач для нелінійних еліптичних рівнянь, які можна подати у вигляді нелінійних операторних рівнянь з монотонним, антитонним чи гетеротонним оператором та для яких доведено існування єдиного додатного розв’язку та побудовано двобічні наближення до нього. Удосконалено метод побудови конусного відрізку при дослідженні крайових задач для нелінійних еліптичних рівнянь, права частина яких перетворюється на нуль на лівому кінці конусного відрізку. Набув подальшого розвитку метод квазіфункцій Гріна, а також метод дослідження нелінійних крайових задач з двома та більшою кількістю параметрів. Розглянуті методи можуть бути використані для відшукання розв’язків прикладних задач, математичними моделями яких є крайові задачі для нелінійних еліптичних рівнянь. Modern science is highly interested in processes that take place in nonlinear environments. Mathematical models of these processes typically are represented by nonlinear boundary value problems of mathematical physics, often with parameters. The development and application of two-sided methods and the Green's quasifunction method to the solution of specific boundary value problems for nonlinear elliptic equations is an actual scientific task. The thesis is devoted to the development of constructive methods of searching positive solutions of one class of boundary value problems for nonlinear elliptic equations and finding the conditions that the parameters of the problem must satisfy in order to guarantee the existence and uniqueness of the solution as well as the convergence of the corresponding iterative process. To achieve this goal the following tasks need to be solved: reduce the nonlinear elliptic boundary value problem to the operator equation; investigate the properties of the operator of the obtained equation by means of the nonlinear analysis methods in partially ordered spaces, in particular, monotonicity, antitonicity or heterotonicity; investigate the possibility of constructing an invariant conical interval for a monotone operator and a strongly invariant one for the antitone or the heterotone operator containing the solution of the initial boundary value problem and provide the procedure for its construction explicitly; investigate the operator on the concavity (for the monotone operator) or pseudoconcavity (for the antitone or the heterotone operator); investigate the operator on the 0u-concavity (for the monotone operator) or 0u-pseudoconcavity (for the antitone or the heterotone operator) in order to be able not only draw to conclusions about the existence of a single solution, but also to impose conditions on the parameters included in the problems; develop the Green's quasifunction method for its application to the problems under consideration in case two-sided approximations can’t be obtained; conduct a series of computational experiments for each of the problems in various domains. The research methods are based on the use of the methods of the operator equations theory in partially ordered spaces to find approximate solutions, the mathematical apparatus of the R functions theory to construct normalized equations of domains boundary in which boundary value problems are considered, the Green's quasifunction method to reduce a nonlinear boundary value problem to a nonlinear integral equation, the formulas of the numerical integration and the function interpolation. The research carried out in the dissertation allowed us to obtain the following new scientific results: for the first time one class of boundary value problems for nonlinear elliptic equations has been highlighted for which these problems can be represented as nonlinear operator equations with a monotone, antitone or heterotone operator, the existence of a unique positive solution has been proved using the methods of the operator equations theory in partially ordered spaces and two-sided approximations has been constructed that converge to this solution; the method of constructing a conical interval has been improved in the case of investigation of boundary value problems for nonlinear elliptic equations when the right side of the equation turns into zero on the left end of a conical interval in terms of the application of the R functions theory apparatus to the construction of the left end of a conical interval, which has made it possible to transform the inevitably one-sided process of successive approximations into the two-sided one; the Green's quasifunction method has been further developed in terms of its application to the solution of nonlinear boundary value problems in domains for which the Green's function analytical expression is unknown or it has a complex form for computations; the method of investigation of nonlinear boundary value problems with two and more parameters has been further developed in terms of the application of nonlinear analysis methods in partially ordered spaces to find the conditions which these parameters must satisfy in order to have a single positive solution to exist and two-sided successive approximations to converge to it.
Keywords: функція Гріна; квазіфункція Гріна; двобічні наближення; інваріантний конусний відрізок; сильноінваріантний конусний відрізок; угнутість; u -угнутість; псевдоугнутість; монотонний оператор; антитонний оператор; гетеротонний оператор; Green’s function; Green’s quasifunction; two-sided approximations; invariant conical interval; strongly invariant conical interval; concavity; u -concavity; pseudoconcavity; u -pseudoconcavity; monotone operator; antitone operator; heterotone operator